European Respiratory Society International Congress, Paris, 2018: highlights from the Clinical Assembly - Vanfleteren, Lowie E.G.W.; Kahn, Nicolas (ERJ Open Research, 2019)
This article contains highlights and a selection of the scientific advances from the European Respiratory Society's Clinical Assembly (Assembly 1 and its five respective groups) that were presented at the 2018 European Respiratory Society International Congress in Paris, France. The most relevant topics from each of the groups will be discussed, covering a wide range of areas including clinical problems, rehabilitation and chronic care, thoracic imaging, interventional pulmonology, and general practice and primary care. The newest research, actual data and highlight sessions will be discussed. - Tweetable abstract ERSpublications - click to tweetA highlights review of selected presentations from #ERSCongress 2018 by the @ERStalk Clinical Assembly http://ow.ly/70Xu30mZ6t9